2019
DOI: 10.1021/acs.iecr.8b05889
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design Procedure of Dual-Reflux Pressure Swing Adsorption Units for Nonlinear Separations

Abstract: In the frame of dual-reflux pressure swing adsorption processes, design strategies applicable to the complete separation of binary gas mixtures are available only in the case of linear adsorption isotherms. Therefore, in this work we propose a simple and efficient design procedure which enables the selection of suitable operating conditions when sharp separation is required and Langmuir adsorption isotherms are involved. Starting from the available strategy for the linear adsorption case, we adapt it to the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The modelling results were in excellent agreement with the experiments. Rossi et al [32,33] developed a detailed single-bed model using the Finite Volume discretization method (FVM). The FVM model was found to be in good agreement with literature data despite the fact that it assumed isothermal conditions and neglected axial dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…The modelling results were in excellent agreement with the experiments. Rossi et al [32,33] developed a detailed single-bed model using the Finite Volume discretization method (FVM). The FVM model was found to be in good agreement with literature data despite the fact that it assumed isothermal conditions and neglected axial dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, reliable simplified approaches to the design of DRPSA processes are not available. As a matter of fact, most contributions from the literature, involving either experiments or mathematical models, designed DRPSA processes through either trial-and-error approaches or using many oversimplifying assumptions. Among the latter approaches, it is worth mentioning the so-called equilibrium theory. ,,,,, Even if this approach can predict the effect of changing the main design parameters, the results are reliable provided the fulfillment of major assumptions, such as instantaneous equilibrium conditions, linear equilibrium isotherms, ideal gas behavior, ideal plug flow conditions in the fixed-bed, isothermal operation, negligible pressure drop, and complete separation of the two components of the mixture.…”
Section: Introductionmentioning
confidence: 99%
“…Several simulation studies on DR‐PSA have been reported, ranging from simplified analytical models 17,33–38 to rigorous nonisothermal numerical models 26–28,39–44 . Based on the equilibrium theory, 45 simplified analytical models revealed critical insights into the operating parameters and separation performance of DR‐PSA.…”
Section: Introductionmentioning
confidence: 99%
“…Following the seminal DR-PSA apparatus demonstrated by Diagne et al, 14,18,19 extensive experimental results have indicated the potential and efficacy of DR-PSA processes at the separation of different binary mixtures, such as air separation, 20,21 hydrocarbon concentration, [22][23][24][25][26][27][28] and CO 2 capture. [29][30][31][32] Several simulation studies on DR-PSA have been reported, ranging from simplified analytical models 17,[33][34][35][36][37][38] to rigorous nonisothermal numerical models. [26][27][28][39][40][41][42][43][44] Based on the equilibrium theory, 45 simplified analytical models revealed critical insights into the operating parameters and separation performance of DR-PSA.…”
mentioning
confidence: 99%